Integration of Environmental Education Through Ecopedagogical Approach to Social Studies - Rohsulina, Pranichayudha; Setyowati, Dewi Liesnoor; Priyanto, Agustinus Sugeng; Utomo, Cahyo Budi (Universitas Negeri Semarang, 2024)
This research was conducted based on the importance of environmental education in learning Social Sciences in junior high schools, especially in developing students' knowledge through the learning process. This research focuses on observing the implementation of environmental education for junior high school students in learning Social Sciences using an ecopedagogy approach. The purpose of this study is to determine the development of the implementation of environmental education in learning Social Sciences with an ecopedagogy approach. The research was conducted in junior high schools throughout Sukoharjo Regency, which have the predicate of public schools or non-aghiwiyata and adhiwiyata schools. This study used a descriptive qualitative method with the research subjects being all social studies teachers and vice principals of the curriculum division. The results showed that through the process of conducting interviews with related parties, it was shown that the implementation at junior high schools in Sukoharjo district varied quite well, with quite good results in the implementation of environmental education and some that produced quite low results in the implementation of environmental education in learning social sciences.